Variations in population structure in the genus Tetraclita (Crustacea: Cirripedia) between temperate and tropical populations. III. T. stalactifera in Costa Rica - Villalobos, Carlos R. (Revista de Biología Tropical, 1980)
Studies on the population structure of the cirriped Tetraclita stalactifera were conducted at two localities in Bahía Ballena, Nicoya Península, Costa Rica. The results indicate that reproduction occurs every year. Well-developed gonads are present from April through August, the nauplii being clearly defined in October and November. Release of larvae takes place in late November and early December. As in California, the individuals reproduce the year after they reach sexual maturity. The relative density is fairly constant through the year showing values slightly higher than those observed in northern populations. Mortality is heavy in the youngest size classes. It appears to be extemely low in individuals with a test diameter over 25 mm, in particular because of the lack of large predators.